Rapid prototyping of grating magneto-optical traps using a focused ion beam - Sun, Xiao; Rickard, William; Sparkes, Ben; White, Ben; Offer, Rachel; Luiten, Andre; Ironside, Charlie (2021)
We have developed a rapid prototyping approach for creating custom grating magneto-optical traps using a dual-beam system combining a focused ion beam and a scanning electron microscope. With this approach we have created both one- and two-dimensional gratings of up to 400 µm × 400 µm in size with structure features down to 100 nm, periods of 620 nm, adjustable aspect ratios (ridge width : depth ∼ 1 : 0.3 to 1 : 1.4) and sidewall angles up to 71°. The depth and period of these gratings make them suitable for holographic trapping and cooling of neutral ytterbium on the 1S0 → 1P1 399 nm transition. Optical testing of the gratings at this wavelength has demonstrated a total first order diffraction of 90% of the reflected light. This work therefore represents a fast, high resolution, programmable and maskless alternative to current photo and electron beam lithography-based procedures and provides a time efficient process for prototyping of small period, high aspect ratio grating magneto-optical traps and other high resolution structures.